The Distinguishing Characteristics of Temporary and Permanent Layoffs - Haltiwanger, John (Journal of Labor Economics, 1984)
This paper develops a theory of layoffs in an intertemporal setting in which job separations may occur in each of several successive periods. Theoretical analysis of temporary layoffs in previous studies has been limited to models in which the layoffs occur only in the final period of the model. This multiperiod implicit contract framework enables us to identify distinguishing characteristics of temporary and permanent layoffs that were heretofore blurred or distorted in previous contract analyses.